Opioid receptor desensitization: mechanisms and its link to tolerance - Allouche, Stéphane; Noble, Florence; Marie, Nicolas (Frontiers in Pharmacology, 2014)
Opioid receptors are part of the class A of G-protein coupled receptors and the target of the opiates, the most powerful analgesic molecules used in clinic. During a protracted use, a tolerance to analgesic effect develops resulting in a reduction of the effectiveness. So understanding mechanisms of tolerance is a great challenge and may help to find new strategies to tackle this side effect. This review will summarize receptor-related mechanisms that could underlie tolerance especially receptor desensitization. We will focus on the latest data obtained on molecular mechanisms involved in opioid receptor desensitization: phosphorylation, receptor uncoupling, internalization and post-endocytic fate of the receptor.